2015
DOI: 10.1177/2055217315585333
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to behavioural interventions in multiple sclerosis: Follow-up meeting report (AD@MS-2)

Abstract: After an initial meeting in 2013 that reviewed adherence to disease modifying therapy, the AD@MS group conducted a follow-up meeting in 2014 that examined adherence to behavioural interventions in MS (e.g. physical activity, diet, psychosocial interventions). Very few studies have studied adherence to behavioural interventions in MS. Outcomes beyond six months are lacking, as well as implementation work in the community. Psychological interventions need to overcome stigma and other barriers to facilitate initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Moreover, we observed different patterns of adherence in distinct pathologies: with a better adherence in PD and stroke than in MS. This lower adherence to treatment of the MS group might be due to the fatigue that this population experiences during treatment and in daily life (54). It is known that MS patients are faced with elevated challenges when following long-term intervention and there is an urgent need of future research focusing on solutions for continuity of care and exercise persistence in the MS population (55, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed different patterns of adherence in distinct pathologies: with a better adherence in PD and stroke than in MS. This lower adherence to treatment of the MS group might be due to the fatigue that this population experiences during treatment and in daily life (54). It is known that MS patients are faced with elevated challenges when following long-term intervention and there is an urgent need of future research focusing on solutions for continuity of care and exercise persistence in the MS population (55, 56).…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that healthy lifestyle is associated with better health outcomes in people with MS, little is known about longterm adherence to behavior change interventions for people with MS [20]. We aimed to assess barriers and enablers to long-term adherence in people with MS who self-enrolled in a healthy lifestyle intervention.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, multimodal intervention studies are scarce, even though they may be most effective [18], and effects may be multiplicative. In addition, as many trials lack longitudinal follow-up [19], an international multidisciplinary working group has called for more research in this area [20]. Lifestyle intervention trials can be difficult to design and conduct [21], but such evidence is needed to enable a shift in MS management towards a more holistic approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…A survey showed that 85% of 199 surveyed PwMS in the United States were willing to try a dietary intervention for at least 3 months[ 9 ]. However, few trials measure adherence, for example lifestyle changes, and outcomes beyond 12 months[ 10 ]. Furthermore, while many interventions in MS have focussed on a single health behaviour such as diet or physical activity, there is some evidence that a multimodal intervention, targeting a variety of risk-factors at once, may have benefits over and above the sum of benefits[ 11 ].…”
Section: Introductionmentioning
confidence: 99%